Magnetic Resonance Imaging in Childhood Primary Hypertension: Potential in the Study of Cognitive Outcomes. Issue 3 (11th February 2021) - Uddin, Md Nasir; Tivarus, Madalina; Adams, Heather; Little, Erika; Schifitto, Giovanni; Lande, Marc B.
Abstract : Primary hypertension in youth and young adulthood is associated with decreased neurocognitive test performance both in midlife and during youth itself, leading to concern of subsequent cognitive decline and dementia in later life. The early vascular effects of hypertension in youth are likely involved in the pathogenesis of hypertensive target organ damage to the brain, but the potential impact of antihypertensive treatment from youth on subsequent cognitive health is not known. This review will highlight the need to answer the question of whether treatment of hypertension from early in life would slow cognitive decline in adulthood, and will then outline, for the nonneurologist, magnetic resonance imaging techniques potentially useful in the study of the pathogenesis of decreased cognition in hypertensive youth and for use as potential biomarkers for early antihypertensive treatment interventions.